Development of Model for Heating Process of Herb Drying Based on Linear System Identification - Samsuhidin, Antonio Orlando; Hamdan, Rohaiza; A. Jalil, Mohd Hafiz (Evolution in Electrical and Electronic Engineering, 2023)
The development of drying herbs by heating is a dynamic process that can be described and optimized using linear system identification. This method involves collecting data from the system, such as temperature and humidity, and using it to identify mathematical models that characterize the system’s behaviour. Specifically, the ARX (AutoRegressive with Exogenous inputs) and ARMAX (AutoRegressive with Exogenous inputs and Moving Average) models are commonly used in this process. These models involve using historical data on the system’s inputs and output to make predictions and identify relationships between the different variables. After a model has been identified, it can be utilized to make predictions regarding the system’s reaction to various inputs and conditions, such as variations in the system’s temperature or humidity. This can help to improve the quality, energy conservation, and efficiency of the drying process. However, traditional open-loop or linear control systems lack the necessary feedback capability, which can lead to a reduction in the shelf life of the herbs. Therefore, it is important to study and compare different pre-drying and drying procedures to find the best method for each type of herb. The main goal of this paper is to collect data, create a mathematical model based on linear system identification using ARX and ARMAX models, and propose a controller that can automatically control the temperature of the herb drying process.